Genetic Connectivity of Seamount Populations of Bluenose Warehou (Hyperoglyphe antarctica) - Heyworth, Stephanie M.; Bell, James B.; Wade, Christopher M.; Cavalcante, Geórgenes; Robinson, Nicholas; Young, Emma; Glass, James; Feary, David A. (Frontiers in Marine Science, 2021)
Quantifying the level of population connectivity within and between geographically separated single-species deep-water fisheries stocks will be vital for designing effective management plans to preserve such populations. Despite this, stock structure in many fisheries is still poorly described and, at best, subject to precautionary management. Here we use rapidly evolving mitochondrial genes and microsatellite markers to investigate population connectivity patterns in commercially targeted Hyperoglyphe antarctica populations between four seamounts within the Tristan da Cunha Exclusive Economic Zone (EEZ). We find little evidence of population genetic structure between fished populations, with both mtDNA and microsatellite markers showing that there is low genetic population diversity (reflecting substantial gene flow) across the four seamounts. We also find little genetic differentiation between H. antarctica across the wider Southern Hemisphere. Such results support the role for coordinated management of all four populations across the seamounts, and potentially including stocks associated with Australia and New Zealand, with expansion of the fishery clearly having the potential to substantially impact the source of recruits and therefore wider population sustainability.